Wychowawcza rola aktywności fizycznej – analiza procesu socjalizacji osób z niepełnosprawnością w sporcie i przez sport - Całek, Grzegorz; Niedbalski, Jakub; Racław, Mariola; Żuchowska-Skiba, Dorota; Agnieszka Gralak (Understanding Disability: Issues, Research, Reflections, 2021)
Purpose of the conducted research was to analyze a processual dimension of transformations of a disabled person’s life, which take place under influence of experiences related to sport practicing. In the article I try to prove similarity of the sport structure with the educational system structure, where apart of the strictly educational functions, there are also socialization processes taking place, diverse in terms of measures and results. A basis for realization of the purpose mentioned above were personal experiences of the researched individuals. Hence, the research exploits qualitative data, collected during participant observations and in-depth free interviews, conducted among the disabled practicing sports. Analysis and interpretation of the research material was performed in accordance with procedures of the grounded theory. The article has been prepared as a consequence of research carried out between 2012 and 2015, among a society of the disabled, who practice professional sports. The studies refer to characteristics of the sport career path of persons with disabilities, which regarding its specificity, has strong roots in institutionalized practices related to inclusion, continuance and maintenance of the main action, i.e. sport practicing.